Weight changes and the risk of knee osteoarthritis requiring arthroplasty - Manninen, P (2004)
Objective: To examine the effect of weight changes between 20 and 50 years of age on the risk of severe knee osteoarthritis (OA) requiring arthroplasty. Subjects and methods: Cases were 55–75 year old men and women (n = 220) having had knee arthroplasty for primary osteoarthritis at the Kuopio University Hospital in 1992–93. Controls (n = 415) were randomly selected from the population of Kuopio Province. Weight at the age of 20, 30, 40, and 50 years was collected retrospectively with a postal questionnaire. Results: After adjustment for age, sex, history of physical workload, recreational physical activity, and previous knee injury, weight gain resulting to a shift from normal body mass index (BMI ⩽25 kg/m(2)) to overweight (BMI >25 kg/m(2)) was associated with a higher relative risk of knee OA requiring arthroplasty than persistent overweight from 20–50 years of age, compared with those with normal relative weight during the corresponding age period. The odds ratios (OR) were 3.07 (95% confidence interval 1.87 to 5.05) for those with normal weight at the age of 20 years and overweight at two or three of the ages 30, 40 or 50 years, 3.15 (1.85 to 5.36) for those with overweight from the age of 30 years, and 2.37 (1.21 to 4.62) for those with overweight from the age of 20 years, respectively. Conclusion: In adult life, a shift from normal to overweight may carry a higher risk for knee OA requiring arthroplasty than does constant overweight.